The inner game of music - Green, Barry, 1945-; Gallwey, W. Timothy (Garden City, N.Y. : Anchor Press/Doubleday, 1986)
Suggests techniques for overcoming self-consciousness and improving musical performances, shares a variety of exercises, and includes advice on improving one's listening skills.
-- Introduction / W. Timothy Gallwey -- The Mozart in us -- The inner game -- The inner game skills -- The power of awareness --The power of will -- The power of trust -- Letting go -- Coping with obstacles -- Improving the quality of musical experience --Teaching and learning -- The inner game listener -- Parent and coach -- Integration and balance -- Ensemble playing -- Improvisation, composition, and creativity.
Keywords: Music -- Performance -- Psychological aspects